MOTIVATION OF FARMER GROUP MEMBERS IN CULTIVATING ORGANIC VEGETABLES - Lantarsih, Retno; Manggala, Setyaji; Kadarso, Kadarso; Subeni, Subeni (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2022)
The increasing demand for organic vegetables is a business opportunity. Organic farmer groups use this opportunity to supply organic vegetables in the Yogyakarta area. This study aims to determine farmers' motivation level in organic vegetable cultivation and the relationship between internal and external factors with farmer motivation. This research is descriptive. The study focused on the Tranggula Farmers Group and the Merapi Organic Farmers Group as farmer groups that supply organic vegetables in several supermarkets in the Special Region of Yogyakarta. The analysis method uses class intervals and Spearman correlation. The motivations in this study include economic, social, and self-actualization motivations. The results showed that farmers' motivation for actualization is a priority in cultivating organic vegetables. There are 63.3% of farmers who have very high actualization motivation, 26.7% of farmers who have very high social motivation, and 16.7% of farmers who have a very high economic motivation. Farmers' motivation level in organic vegetable cultivation is in the high category of 60% and very high at 40%. The experience of farmers has a weak and contradictory relationship with the motivation of farmers to cultivate organic vegetables. Meanwhile, other internal factors, namely age, education, and external factors consisting of the provision of production facilities, assistance, and market guarantees, have no relationship with the motivation of farmers to cultivate organic vegetables.